2008
DOI: 10.1111/j.1545-5300.2008.00254.x
|View full text |Cite
|
Sign up to set email alerts
|

Factorial and Construct Validity of the Revised Short Form Integrative Psychotherapy Alliance Scales for Family, Couple, and Individual Therapy

Abstract: The Integrative Psychotherapy Alliance model brought an interpersonal and systemic perspective to bear on theory, research, and practice on the psychotherapeutic alliance. Questions have been raised about the independence of the theoretical factors in the model and their operationalization in the Individual, Couple, and Family Therapy Alliance Scales. This paper presents results of a confirmatory factor analysis of the scales that delineated at least three distinct interpersonal factors as well as shorter vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
157
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(169 citation statements)
references
References 27 publications
10
157
0
2
Order By: Relevance
“…Limitations of this review include a lack of attention to the working alliance construct in specific populations or types of therapy, including child/ adolescent (McLeod, 2011) and couples and family therapy (Pinsof et al, 2008). An in-depth discussion of the impact of different reporters and the convergence of patient, therapist, and observer-based measures was also beyond the scope of this paper.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Limitations of this review include a lack of attention to the working alliance construct in specific populations or types of therapy, including child/ adolescent (McLeod, 2011) and couples and family therapy (Pinsof et al, 2008). An in-depth discussion of the impact of different reporters and the convergence of patient, therapist, and observer-based measures was also beyond the scope of this paper.…”
Section: Resultsmentioning
confidence: 98%
“…Of note, measures also exist that extended beyond the individual psychotherapy paradigm, including the Couple Therapy Alliance Scale and the Family Therapy Alliance Scale (CTAS and FTAS; Pinsof & Catherall, 1986). The most recently revised versions of these measures include the CTAS RevisedShort Form (CTASr-SF) and FTAS Revised-Short Form (FTASr-SF), which include interpersonal dimensions of the alliance and assess the perception of significant others of the therapeutic relationship (Pinsof, Zinbarg, & Knobloch-Fedders, 2008).…”
Section: Measurementmentioning
confidence: 99%
“…Quinn, Dotson, and Jordan (1997) stated that "with two or more clients, couple and family therapy creates a social field that presents unique challenges, demands, and processes not found in individual psychotherapy" (p. 430). For example, instead of viewing the alliance individualistically, the therapeutic alliance must be considered in terms of the couple relationship (Rait, 2000), meaning that Attachment and the Therapeutic Alliance 217 the therapist's actions in joining with one member of the couple subsystem could have a simultaneous effect on the other member (Pinsof, Zinbarg, & Knobloch-Fedders, 2008). Thus, the therapist must focus on the relationship between himself and each client, as well as the relationship between the clients, which makes establishing an effective therapeutic alliance more difficult and complex.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Webb et al (2011), found that the agreement on tasks and goals factor is a better predictor of symptomatic changes in CBT than the relationship factor (bond). Meanwhile, other studies found a positive relationship between the bond dimension of the alliance and outcome in interpersonal therapies (Wettersten, Lichtenberg, & Mallinckrodt, 2005), and between bond and clients' sense of well-being and decrease in symptoms (Pinsof, Zinbarg, & Knobloch-Fedders, 2008). Furthermore, Le Coco, Gullo, Prestano, and Gelso (2011), describe a positive significant relationship between clients' early assessment of authenticity of their relationship with their therapists and the bond dimension, and therapy outcome in brief psychodynamic therapies.…”
Section: The Alliance As a Multi-dimensional Phenomenonmentioning
confidence: 91%